Tumor Targeting, Pharmacokinetics and Biodistribution of a Near Infrared Fluorescent-labeled δ-Opioid Receptor Antagonist Agent, Dmt-Tic-Cy5 - Huynh, Amanda Shanks (Mol Pharm, 2016)
Fluorescence molecular imaging can be employed for the development of novel cancer targeting agents. Herein, we investigated the pharmacokinetics (PK), biodistribution (BD) and cellular uptake of Dmt-Tic-Cy5, a delta-opioid receptor (δOR) antagonist-fluorescent dye conjugate, as a tumor-targeting molecular imaging agent. δOR expression is observed normally in the CNS, and pathologically in some tumors, including lung liver and breast cancers. In vitro, in vivo and ex vivo experiments were conducted to image and quantify the fluorescence signal associated with Dmt-Tic-Cy5 over time using in vitro and intravital fluorescence microscopy and small animal fluorescence imaging of tumor-bearing mice. We observed specific retention of Dmt-Tic-Cy5 in tumors with maximum uptake in δOR-expressing positive tumors at 3 h and observable persistence for >96 h; clearance from δOR non-expressing negative tumors by 6 h; and systemic clearance from normal organs by 24 h. Live-cell and intravital fluorescence microscopy demonstrated that Dmt-Tic-Cy5 had sustained cell-surface binding lasting at least 24 h with gradual internalization over the initial 6 h following administration. Dmt-Tic-Cy5 is a δOR-targeted agent that exhibits long lasting and specific signal in δOR-expressing tumors, is rapidly cleared from systemic circulation and is not retained in non-δOR expressing tissues. Hence, Dmt-Tic-Cy5 has potential as a fluorescent tumor imaging agent.